Abu Al-Aswad Al-Du’ali: Pencipta Ilmu Nahu: Abu Al-Aswad Al-Du’ali: Creator of the Science of Grammar - Ali, Mohd Bakhit; Abd Rahman, Mohd Muhiden (Al-Basirah Journal, 2021)
The objective of this article is to explore the biography of Abu Aswad and to analyse his contribution in pioneering the knowledge of Arabic grammar and the factors of its creation. Abu Aswad is one of the well known Arab scholars in Arabic linguistic. He contributed to Islamic world by pioneering the knowledge of Arabic grammar. The methodology is this article is based on library method. Through this method, all the data is referred to and collected from library sources related to the topic. The referred data is derived from trusted primary or secondary sources. The outcome of this study verifies the huge contribution made by Abu Aswad to the Arabic linguistic by pioneering the study of Arabic grammar. Knowledge of Arabic grammar is essential for anyone who wishes to explore the vast literature of Arabic language whether in religious, literature, historic and other context.